Nitrogen Deposition Reduces the Diversity and Abundance of cbbL Gene-Containing CO2-Fixing Microorganisms in the Soil of the Stipa baicalensis Steppe - Qin, Jie; Li, Ming; Zhang, Haifang; Liu, Hongmei; Zhao, Jianning; Yang, Dianlin (Frontiers in Microbiology, 2021)
CO2 fixation by autotrophic microbes has a significant effect on the carbon cycle in temperate grasslands. Nitrogen (N) deposition in soil has been steadily increasing for decades, which has consequences for soil microorganisms. However, the impact of this deposition on the diversity and abundance of CO2-fixing soil microorganisms remains unclear in temperate grasslands. In the present study, the cbbL gene, a key gene in the Calvin-Benson-Bassham cycle that encodes the large subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase, was used to study CO2-fixing microbes under different rates of N addition (0, 15, 30, 50, 100 and 150 kg N ha-1 yr-1) in a 9-yr field experiment in a temperate grassland. The results showed that N addition led to significant reductions in cbbL gene abundance and genetic diversity and altered cbbL gene community composition. High N addition enhanced the relative abundances of Acidiferrobacterales and Rhizobiales but reduced those of Burkholderiales and Rhodobacterales. Structural equation modeling further revealed that N addition primarily reduced cbbL genetic diversity by increasing the soil NO3-N content and decreasing the soil pH. N addition indirectly reduced cbbL gene abundance, possibly by increasing the soil N/phosphorus (P) ratio and decreasing the soil pH. These findings suggest that N addition increases the soil available N and causes soil acidification, which may inhibit growth of CO2-fixing microbes to some extent.